Vulnerability detection in smart contact using chaos optimization-based DL model - Vaddadi, Srinivas A; Somanathan Pillai, Sanjaikanth E Vadakkethil; Vallabhaneni, Rohith; Addula, Santosh Reddy; Ananthan, Bhuvanesh (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This research article introduces a deep learning (DL) for identifying vulnerabilities in the smart contracts, leveraging an optimized DL method. The proposed method, termed LogT BiLSTM, combines bidirectional long short-term memory (BiLSTM) with logistic chaos Tasmanian devil optimization (LogT) for enhancing detection of vulnerability. The evaluation of the suggested approach is conducted using publicly available datasets. Initially, preprocessing steps involve removing duplicate data and imputing missing data. Subsequently, the vulnerability detection process utilizes BiLSTM, with the optimization of the loss function achieved through LogT. Results indicate promising performance in identifying vulnerabilities in SC, highlighting the efficacy of the LogT-BiLSTM approach.